Approaches to learning Arabic: Theory, concepts and implementation - Isnaini, Isnaini; Maskud, Maskud; Maulana, Asep; Maulana, Bayu Wahyu (Abjadia : International Journal of Education, 2025)
This article is a systematic review of literature that describes the approach as a component in learning, especially in Arabic learning activities. There are two approaches used in the learning process, namely the learning approach with a teacher centered strategy and the learning approach with a student centered strategy. The accuracy of the approach used in learning determines the achievement of the Arabic language learning objectives that have been set in the lesson plan. The learning steps are carried out in accordance with the learning approach used. This article also explains various things related to the Arabic language learning approach as well as the weaknesses and strengths of the teacher centered and student centered learning approaches.